2009
DOI: 10.1002/aur.78
|View full text |Cite
|
Sign up to set email alerts
|

Impairments on “open‐ended” executive function tests in autism

Abstract: The executive function (EF) theory of autism has received much support recently from a growing number of studies. However, executive impairments have not always been easy to identify consistently and so novel "ecologically valid" tests have been designed which tap into real-life scenarios that are relevant to and representative of everyday behavior. One characteristic of many of these tasks is that they present the participant with an "ill-structured" or "open-ended" situation. Here, we investigated the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
83
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 62 publications
(81 reference statements)
9
83
2
4
Order By: Relevance
“…With this caveat, we argue that in general terms our findings support those of others who have found multitasking difficulties in ASD (Emslie et al, 2003;Hill & Bird, 2006;MacKinlay et al, 2006;White et al, 2009). More importantly, these findings have arisen from the use of a novel paradigm involving a virtual environment that couples simulation of a real environment with the scientific control of a laboratory setting for testing participants and collecting high quality data.…”
Section: Multitasking In Hf-asd Using the Virtual Errands Task 17supporting
confidence: 90%
See 4 more Smart Citations
“…With this caveat, we argue that in general terms our findings support those of others who have found multitasking difficulties in ASD (Emslie et al, 2003;Hill & Bird, 2006;MacKinlay et al, 2006;White et al, 2009). More importantly, these findings have arisen from the use of a novel paradigm involving a virtual environment that couples simulation of a real environment with the scientific control of a laboratory setting for testing participants and collecting high quality data.…”
Section: Multitasking In Hf-asd Using the Virtual Errands Task 17supporting
confidence: 90%
“…Our ASD participants also performed more poorly on the Modified Six Elements Test sub-task of the BADS, a finding that provides some cross-validation of the novel VET task for assessing ASD. It is also a finding that is consistent with Emslie et al, 2003, Hill & Bird, 2006and White et al, 2009 participants all demonstrated difficulties with either adult or child versions of that test.…”
Section: Multitasking In Hf-asd Using the Virtual Errands Task 17supporting
confidence: 84%
See 3 more Smart Citations